2020
DOI: 10.2196/17550
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence-Based Differential Diagnosis: Development and Validation of a Probabilistic Model to Address Lack of Large-Scale Clinical Datasets

Abstract: Background Machine-learning or deep-learning algorithms for clinical diagnosis are inherently dependent on the availability of large-scale clinical datasets. Lack of such datasets and inherent problems such as overfitting often necessitate the development of innovative solutions. Probabilistic modeling closely mimics the rationale behind clinical diagnosis and represents a unique solution. Objective The aim of this study was to develop and validate a pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…8 There is a simplification of the dynamic aspect through the reduction of temporal features to the characteristic "duration" of sign (e.g., of fever). 9 Sometimes, for manifestations and diagnoses in the KB a step-by-step development of each manifestation (symptom) is represented, corresponding to one known deviation, but with an already defined time step (the segment is divided into N equal intervals). 10 Sometimes time constraints are introduced for pairwise nonintersecting intervals, which allows one to determine the allowed distance between the corresponding time instants using expressions of temporal logic.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 There is a simplification of the dynamic aspect through the reduction of temporal features to the characteristic "duration" of sign (e.g., of fever). 9 Sometimes, for manifestations and diagnoses in the KB a step-by-step development of each manifestation (symptom) is represented, corresponding to one known deviation, but with an already defined time step (the segment is divided into N equal intervals). 10 Sometimes time constraints are introduced for pairwise nonintersecting intervals, which allows one to determine the allowed distance between the corresponding time instants using expressions of temporal logic.…”
Section: Methodsmentioning
confidence: 99%
“…When adapting an ontology (from universal, problem-oriented to concretized in a domain) we have the opportunity to offer experts a more appropriate terminology, in particular, in medicine to "cover" the clinical picture and the development process not only the symptoms fixed at the doctor's appointment, as in most DSS, 9,20,23,24 but alsophysical examination and relevant investigations.…”
Section: The Technology Of Application Of the Ontologymentioning
confidence: 99%
See 1 more Smart Citation
“…We assumed all of these patients presented for care in area with a local disease prevalence equivalent to the national disease prevalence of 11.1%. For patient 1 Building on work by Chishti et al, 15 we chose probabilistic models in consideration of the scarcity of detailed, individual patient data and to take advantage of the depth of published literature on aggregate symptom probabilities. Our approaches to making step-wise diagnostic assessments with incremental information mimic clinical workflows and reflect the need for transparency and accommodation of new information critical to clinical decision-making.…”
Section: Incorporation Of Location and Diagnostic Test Sequencesmentioning
confidence: 99%
“…Addressing these issues, Chishti et al demonstrated the advantages of using flexible probabilistic frameworks built without large-scale clinical datasets to generate ranked differential diagnoses that are more accurate that those developed by physicians. 15 Combining the approaches of this prior work suggests that an appropriate diagnostic support model should rely on easily obtained symptom data, probabilistic frameworks to avoid the need for large-scale datasets, and most importantly, a flexible schema to refine predictions based on provider judgment and the ability to adapt to changes in local prevalence and current diagnostic test performance. To this end, we present a comparison and clinical validation of three such quantitative models as well as an ensemble approach to the diagnosis of COVID-19 in ambulatory and acute care settings.…”
Section: Introductionmentioning
confidence: 99%